Psicanálise e cinema: efeitos e riscos em intervenções psicanalíticas com dispositivos cinematográficos - Penha, Diego Amaral (2016)
This study, we present considerations about the effects and the risks of a psychoanalytic intervention with cinema apparatus. With a clinial-politic researching methodology, we conducted the tension between psychoanalytic theory and cinema theory. The concept of cinema apparatus, present in Jean-Louis Baudry s Works, guided ours reflections on the issue of cinema ideology. The cinema experience is supported by a technical and ideological conditions, provided by it s own basic apparatus of the cinema apparatus. The "impression of reality" is a illusory effect, produced by the apparatus, which has the effect of producing subjectivity. Through the notion of Jacques Lacan's mirror stage, we investigated the identification processes, presents in the first relationships of the Ich with its own image. This notion articulates the formation processes of the Ich , primary narcissism, identification, among others. The childhood fantasys and film s fantasys was articulated with the notion of Spiel . We conclude that the ideological effects of the cinema apparatus, when thinked in conjunction with the notion of identification, may include somekind of Spiel-Raum and political exercise tanking account of the power s mechanisms at work of clinical-politics.pratice